Anti-Listerial Effect of 4-Hydroxyphenylpropanoic Acid Esters Synthesized by Lipase-Catalyzed Esterification - Bartłomiej Zieniuk; Ewa Białecka-Florjańczyk; Agata Fabiszewska (The 1st International Electronic Conference on Food Science and Functional Foods, 2020)
Listeria monocytogenes—A Gram-positive intracellular bacteria is one of the most virulent foodborne pathogens. A common strategy used to control the growth of bacteria in food is using food additives. However, many bacterial species are resistant to food preservatives, and bacterial resistance can be natural or acquired. Therefore, there is a constant need to search for new compounds with antimicrobial properties. The purpose of the present study was to evaluate the efficiency of five (ethyl, butyl, hexyl, octyl, and decyl) esters of 4-hydroxyphenylpropanoic acid against L. monocytogenes PCM 2191. Esters were obtained in reactions catalyzed by Candida antarctica lipase B. Purified esters with structures confirmed by 1H NMR were applied to determine minimal inhibitory concentrations (MIC) using the microdilution broth method. MIC values ranged 0.0625–16 mM. The results of this study have demonstrated the potential application of 4-hydroxyphenylpropanoic acid alkyl esters in inhibiting the growth of L. monocytogenes. Octyl 4-hydroxyphenylpropanoate proved to be the best antimicrobial agent and was used in a time-kill assay with different concentrations of 1 × MIC, 4 × MIC, and 16 × MIC. Three to nine log reduction of cell number were observed compared to control medium without any antimicrobial compound after 24 h, and the possibility of using octyl 4-hydroxyphenylpropanoate in food applications is worth further investigation.